POLITENESS DISTINCTION: TERMS OF ADDRESS USED BY BANJERESE YOUTH IN DAILY LIFE - Dini Noor Arini (Langkawi: Journal of The Association for Arabic and English, 2016)
In Bahasa Banjar, addressing has an important role in the norms ofsociety. It shows the quality of the person who is addressing theaddressee whether he or she is highly educated or not. Banjarese peopleneed to address appropriately due to the culture which is still boundclosely to the society. On the term of politeness, Banjarese also has somediction to show respect in the way they speak. According to Anna (2:2008),“Politeness referent includes the category of titles, polite pronouns, nominal honorifics, and verbal honorifics”. The research is aimed to find out the politeness distinction used by the Banjarese youth in their daily life. The research used the descriptive qualitative method and is conducted to 15 participants randomly. They were given a questionnaire about some indicators related to the politeness distinction in Banjarese culture. The result shows that Pian is used by 15 respondents in addressing the older people and ulun in addressing themselves, Abah and mama are used by 11 respondents to address their parents, while the other 4 use bapak and mama, abah and ibu, papah and mamah, and mama and papap. In addressing their friends, 15 respondents use aku and ikam. In respecting the higher level people such as teacher or lecturer, all the respondents use bapak, ibu, and pian. In conclusion, there are three levels of politeness in addressing the older people in Banjarese: the most polite one; ulun and pian, the less polite one; aku and ikam, and the least polite; nyawa and unda.Keywords: politeness distinction, terms of address, Banjarese youthKeywords: politeness distinction, terms of address, Banjarese youth